Sustainable Research and Community Engagement Model in Indonesian Public Universities: Legal and Policy Perspectives - Irawaty Irawaty; R Benny Riyanto; Dina Silvia Puteri; Nurul Fibrianti; Ridwan Arifin; Wahyudin Wahyudin (Universitas Negeri Semarang, 2026)
Universities must not stand alone and act as institutions that are not related to communities. Education should elevate scholars, not only in terms of thinking but also in terms of giving positive contribution to communities. In Indonesia, there are some types of status of universities, one of them is named public universities with legal entity (PTN-BH). This type of status is also mandated to provide contributions to communities that should be aligned with results of previous research conducted by universties’ scholars or vice versa. Nevertheless, regulations on how research and community engangement through such model may be realized remain limited. Thus, this work aims to establish a model for such research and community engangement by considering the existing policy and regulations. This research used quantitative approach. Data gathered through semi-structured interviews, documents analysis, and case studies from selected PTN-BH. Methods of analyzing data were thematically identified patterns, challenges, and best practices. The findings were: (1) it is essential for PTN-BH to establish robust policy and regulations, (2) constitute how to have sustainable engagement projects between PTN-BH with communities, and (3) determine sustainable mutual benefits. The model that is proposed has been developed through careful consideration of policy and laws that have been there as enabling factors not as barriers. Thus, the contibution of this study is the notion of the necessity of sustainable connection between PTN-BH with community that corresponds with the existing policy and regulations. This aligns with Sustainable Development Goals (SDGs) 4: Quality Education.